Synthesis and facile functionalization of siloxane based hyper-cross-linked porous polymers and their applications in water treatment. (October 2019) - Liu, Ruidong; Yang, Zhizhou; Chen, Shiwei; Yao, Jinshui; Mu, Qiuhong; Peng, Dan; Zhao, Hui
Graphical abstract: Functionalization of porous polymers: Hexaphenyldisiloxane containing SiOSi structures were used to prepare a novel hyper-cross-linked porous polymer via Friedel-Crafts alkylation. A large number of hydroxyl groups were formed in the structure of HCP-K obtained from HCP-DH by alkali treatment, which enables the facile functionalization of it by silane coupling agents. Highlights: A novel hexaphenyldisiloxane-based porous polymer (HCP-DH) has been synthesized. The synthesized polymer exhibits excellent performances in the adsorption of dyes. The modification of HCP-DH can be achieved easily. The amino functionalized polymer has good adsorption property for chromium ions. Abstract: A novel hyper-cross-linked porous polymer based on hexaphenyldisiloxane (HCP-DH) is synthesized through Friedel−Crafts reaction. The surface area of HCP-DH is up to 1084 m 2  g −1, and it exhibits excellent adsorption capacities and reusability in organic dyes removal from water. Additionally, the structure of the synthesized polymer can be adjusted by alkali treatment, forming SiOH groups in the pore structures. The porous polymer can be modified by the reaction of SiOH groups and (3-aminopropyl)methyldiethoxysilane easily, and the amino functionalized porous polymer displays a good property in the field of chromium ion adsorption with an adsorption amount of 44.5 mg g −1 under neutral condition. This method provides a new strategy for the synthesis and functionalization of porous polymers.